Short-term Anoxic Treatment of Litchi Fruit (Litchi chinensis Sonn. cv. Hong Huey) Delays Pericarp Browning and Maintains Physicochemical Quality During Storage - Chairat Techavuthiporn; Amnat Jarerat; Hataitip Nimitkeatkai (The Horticulture Journal, 2023)
The effect of short-term anoxic treatment prior to storage at ambient and cool temperatures on pericarp browning, fruit quality, secondary metabolites, antioxidant activity, and the browning enzyme of litchi (Litchi chinensis Sonn.) cv. Hong Huey were investigated. Litchi fruit were exposed to anoxic conditions for 6, 12, 18 and 24 h before storage at 28 ± 2°C for 5 days, or at 7 ± 2°C for 14 days. Anoxic treatment resulted in significantly decreases in electrical conductivity, weight loss, browning index, while maintaining the total soluble solids (TSS) and delaying increases in polyphenol oxidase (PPO) and peroxidase (POD) activities compared with control fruit. Furthermore, anoxic treatment increased litchi pericarp methanol extract antioxidant capacity, as measured by free-radical scavenging activity. This is associated with greater amounts of ascorbic acid, anthocyanins, and phenolic/flavonoid components as compared with control fruit. Additionally, anoxic treatment considerably delayed litchi fruit pericarp browning. This suggests that with adequate short-term anoxia duration, an enhanced non-enzymatic antioxidant process may directly or indirectly delay litchi pericarp browning. Thus, a short anoxic treatment enables harvested litchi quality to be sustained at ambient and cool temperatures. This non-chemical and inexpensive treatment deserves further development and application, especially in commercial distribution systems where cooling is insufficient.
Keywords: Postharvest Quality and Shelf Life Management; Plant Physiology and Cultivation Studies; Phytochemicals and Antioxidant Activities